KCNQ Current Contributes to Inspiratory Burst Termination in the Pre-Bötzinger Complex of Neonatal Rats in vitro - Revill, Ann L.; Katzell, Alexis; Del Negro, Christopher A.; Milsom, William K.; Funk, Gregory D. (Frontiers in Physiology, 2021)
The preBötzinger Complex (preBötC) of the ventral medulla generates the mammalian inspiratory breathing rhythm. When isolated in explants and deprived of synaptic inhibition, the preBötC continues to generate inspiratory-related rhythm. Mechanisms underlying burst generation have been investigated for decades, but cellular and synaptic mechanisms responsible for burst termination have received less attention. KCNQ-mediated K+ currents contribute to burst termination in other systems, and their transcripts are expressed in preBötC neurons. Therefore, we tested the hypothesis that KCNQ channels also contribute to burst termination in the preBötC. We recorded KCNQ-like currents in preBötC inspiratory neurons in neonatal rat slices that retain respiratory rhythmicity. Blocking KCNQ channels with XE991 or linopirdine (applied via superfusion or locally) increased inspiratory burst duration by 2-3 fold. By contrast, activation of KCNQ with retigabine decreased inspiratory burst duration by ~35%. These data suggest that the KCNQ current in preBötC neurons contributes to inspiratory burst termination.